2010
DOI: 10.1152/ajpheart.00779.2009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for enhanced M3 muscarinic receptor function and sensitivity to atrial arrhythmia in the RGS2-deficient mouse

Abstract: Atrial fibrillation (AF) is the most common arrhythmia seen in general practice. Muscarinic ACh receptors (M2R, M3R) are involved in vagally induced AF. M2R and M3R activate the heterotrimeric G proteins, G(i) and G(q), respectively, by promoting GTP binding, and these in turn activate distinct K(+) channels. Signaling is terminated by GTP hydrolysis, a process accelerated by regulator of G protein signaling (RGS) proteins. RGS2 is selective for G(q) and thus may regulate atrial M3R signaling. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 43 publications
(53 reference statements)
1
44
1
Order By: Relevance
“…CTS effects to increase RGS2 expression may influence (Tuomi et al, 2010). We found that digoxin caused RGS2-dependent suppression of M 3 receptor signaling (Fig.…”
mentioning
confidence: 73%
“…CTS effects to increase RGS2 expression may influence (Tuomi et al, 2010). We found that digoxin caused RGS2-dependent suppression of M 3 receptor signaling (Fig.…”
mentioning
confidence: 73%
“…This difference in brain structure resulted in increased anxiety (quantitated by a test for light/darkness preference) and decreased male aggression. Even though no mechanisms were elucidated in how RGS2 might control the various responses in organs, the knockout mice provided a foundation for understanding the physiological functions of RGS2 (Tuomi et al, 2010). Recent genetic quantitative trait analysis has shown that RGS2 is a gene that controls anxiety in mice and possibly humans (Hettema et al, 2013;Le-Niculescu et al, 2011;Lifschytz et al, 2012;Mouri et al, 2010;Muinos-Gimeno et al, 2011;Okimoto et al, 2012;Otowa et al, 2011;Stein et al, 2014;Yalcin et al, 2004).…”
Section: Rgs2mentioning
confidence: 99%
“…Several functional studies have demonstrated the role of RGS4 in the regulation of opioid, cholinergic, and serotonergic receptor signaling in the brain (Fourla et al, 2012;Guasch et al, 2013;Jones et al, 2012;Kong and Tobin, 2011;Leone et al, 2000;Li et al, 2013a;Lifschytz et al, 2012;McOmish et al, 2008;Osterberg et al, 2011;Park et al, 2011;Rivero et al, 2012;Ruiz de Azua et al, 2012a;Stratinaki et al, 2013;Traynor, 2012;Tuomi et al, 2010;Wamsteeker Cusulin et al, 2013;Wang and Traynor, 2011). Upon morphine administration, RGS4 levels rose in the rat LC and decreased immediately after opiate removal.…”
Section: Rgs4mentioning
confidence: 99%
“…Muscarinic receptors are GPCRs (G protein-coupled receptors), and as such they activate heterotrimeric G proteins by catalyzing GDP dissociation from the Gα subunit and consequently promoting GTP binding [17,18]. Regulator of G-protein signaling 2 (RGS2) is a member of a large family of proteins that all regulate signaling through GPCRs by accelerating GTPase [19-21]-activity on active Gα as well as through other mechanisms.…”
mentioning
confidence: 99%
“…Regulator of G-protein signaling 2 (RGS2) is a member of a large family of proteins that all regulate signaling through GPCRs by accelerating GTPase [19-21]-activity on active Gα as well as through other mechanisms. RGS2 has an inhibitory effect on M3-muscarinicacetylcholine receptors (M 3 -mAChRs) [17,22]. M 3 -mAChRs couple to Gαq to activate the G q -phospholipase C (PLC)-protein kinase C (PKC) pathway [23], and the potassium channel I KM3 [23,24].…”
mentioning
confidence: 99%